PENERAPAN PROBLEM BASED LEARNING DALAM PEMBELAJARAN BERBASIS KONSTRUKTIVISME UNTUK MENGEMBANGKAN KEMANDIRIAN SISWA - Harahap, Suaibah Aslamiyah; Ryan Dwi Puspita (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The aim of this study is to describe the implementation of a constructivist approach through the Problem Based Learning (PBL) model in developing the learning independence of fifth-grade students in elementary school on the topic of food chains in IPAS (Science and Environmental Studies) lessons. This research employs a descriptive approach with fifth-grade students as the subjects in an elementary school located in Sei Mencirim, Paya Geli, Sunggal District, Deli Serdang Regency. Data were collected through observations, interviews, and documentation of students' activities during the learning process. The findings of the study indicate that the implementation of constructivist-based learning with the PBL model has a positive contribution to the development of students' learning independence. This can be seen from the seven indicators of learning independence, which include time management, self-assessment of progress, recognizing personal weaknesses, taking responsibility, utilizing learning resources, emotional control, and self-directed learning. The learning design followed six stages of constructivism: situation, grouping, bridging, questioning, demonstration, and reflection, which proved effective in creating an active, collaborative, and meaningful learning environment. Therefore, this approach can be regarded as a relevant and applicable learning strategy to support the achievement of the Merdeka Curriculum objectives.